An Analysis of the Digital Device Access Divide and Its Impact on Junior High School Students’ Learning Process - Nor Azizah; Jasiah Jasiah (The Future of Education Journal, 2026)
Inequality in access to digital devices has become a significant issue in education in the digital era, as junior high school students increasingly depend on digital technologies to obtain information, access learning materials, complete assignments, and communicate with teachers. This study was conducted because previous discussions have primarily focused on online learning in general, while the analysis of disparities in digital device access and their effects on junior high school students’ learning processes remains relatively limited. The study aims to explain the concept of digital device access inequality, its contributing factors, its impact on learning, and potential strategies to address the issue. The research employed a qualitative approach using a library research method. Data were collected through the identification, selection, review, and content analysis of relevant journals, books, reports, and academic documents. The findings indicate that inequality in digital device access is influenced by several factors, including family economic conditions, device quality, internet connectivity, data availability, digital literacy, parental support, and school readiness. These disparities affect students’ opportunities to participate effectively in digital learning environments and may contribute to unequal educational outcomes. The study concludes that equitable access to digital technologies, the strengthening of digital literacy, and the implementation of inclusive school policies are essential prerequisites for ensuring fair and effective learning experiences for junior high school students. Addressing these challenges is crucial for reducing educational disparities and promoting greater equity in digital education.